Fatigue and vibrational analysis of composite plates based on curve fitting method. (2021) - Subash, P.; Nagendharan, S.; Gurusamy, P.; Kishore, R.
Abstract: In this paper studying the fatigue behaviour of race bicycle frames. After a literature study on the fatigue behaviour of composite materials in general, a model dependent on the decrease of firmness was proposed to gets to weakness conduct in bike outlines. To examine this model a fatigue test setup was studied. This specimen was made in accordance with glass fiber, aluminium & fly ash together which some extra features, which can serve for different concepts. The functionality of the setup was evaluated, and this proved to show good results. Also, a fatigue test was carried out on a bicycle and the proposed reduction of stiffness model was validated.